Working conditions of online food delivery gig workers from a consumer perspective in China: A lesson for Malaysia - Yosuke Uchiyama; Md Nasrudin Md Akhir; Yuanzhu Wang; Beatrice Lim; Khairul Hanim Pazim (National Sun Yat-sen University, 2022)
Contemporary Chinese Political Economy and Strategic Relations: An International Journal Vol. 8, No. 2, August 2022 (SCOPUS-Indexed) Whilst the expansion of the gig work market has enabled flexible task-based work that is not bound by employment contracts with firms, it has also given rise to various concerns about the working conditions of gig labours. In China, the general preference for eating out and the convenience of this service has led to a growing need for online food delivery (OFD) services and rising demand for delivery riders. At the same time, the working conditions of the riders are strictly controlled by the oligopoly platforms, which makes their position very weak. However, there is minimal research on how Chinese users understand this situation, generating colossal demand. This study uses primary data collected through in-depth interviews to examine Meituan online food delivery users’ understanding of delivery riders’ working conditions and their potential contribution to empowering riders. Through the thematic analysis, the collected data identified five main themes: new category job location between chance and risk, ultimate O2O productivity labour, fragile workers’ balance of power, and mutual assistance difficulties with 16 sub-categories. Although OFD users had a profound and insightful understanding of riders’ working conditions, their potential contribution to improving working conditions was not highly promising. As platforms continue to be confronted by oligopolies and government regulators, users have a pivotal role as a mitigating factor for the sustainability of China’s on-demand gig economy sector. Lastly, based on the China experience, this article offers lessons to OFD industries in Malaysia.